Cause And Prevention Of Roadway Crashes Among Young, High-Risk Drivers In Malaysia: A Multi-Disciplinary Approach - Giffin Downe, Alan (2008)
The present research was conducted to examine the interaction between the role of behaviour in traffic, some personality constructs, demographic characteristics and driving exposure in predicting crash and injury occurrence.